Methadone, Buprenorphine, and Clonidine Attenuate Mitragynine Withdrawal in Rats - Hassan, Rahimah; Sreenivasan, Sasidharan; Muller, Christian P.; Hassan, Zurina (Frontiers in Pharmacology, 2021)
Background: Kratom or Mitragyna speciosa Korth has been widely used to relieve the severity of opioid withdrawal in natural settings. However, several studies have reported that kratom may by itself cause dependence following chronic consumption. Yet, there is currently no formal treatment for kratom dependence. Mitragynine, is the major psychoactive alkaloid in kratom. Chronic mitragynine treatment can cause addiction-like symptoms in rodent models including withdrawal behaviour. In this study we assessed whether the prescription drugs, methadone, buprenorphine and clonidine, could mitigate mitragynine withdrawal effects. In order to assess treatment safety, we also evaluated hematological, biochemical and histopathological treatment effects. Methods: We induced mitragynine withdrawal behaviour in a chronic treatment paradigm in rats. Methadone (1.0 mg/kg), buprenorphine (0.8 mg/kg) and clonidine (0.1 mg/kg) were i.p. administered over four days during mitragynine withdrawal. These treatments were stopped and withdrawal sign assessment continued. Thereafter, toxicological profiles of the treatments were evaluated in the blood and in organs. Results: Chronic mitragynine treatment caused significant withdrawal behaviour lasting at least 5 days. Methadone, buprenorphine, as well as clonidine treatments significantly attenuated these withdrawal signs. No major effects on blood or organ toxicity were observed. Conclusion: These data suggest that the already available prescription medications methadone, buprenorphine, and clonidine are capable to alleviate mitragynine withdrawal signs rats. This may suggest them as treatment options also for problematic mitragynine/kratom use in humans.
CRIS-Team Scopus Importer:2021-08-06
Keywords: burprenorphine; clonidine; kratom; methadone; mitragynine; replacement; withdrawal